The relation of optical coherence tomography findings with oxidative stress parameters in patients with bipolar disorder and unaffected first-degree relatives - (:unkn) unknown (Elsevier B.V., 2022)
Background: We aimed to evaluate the optical coherence tomography(OCT) findings and oxidative stress parameters in patients with bipolar disorder(BD) and their unaffected first-degree relatives(FDRs) and to explore OCT findings and oxidative stress parameters as potential endophenotype candidates. Methods: Fifty patients with BD, 40 FDRs of BD, and 50 healthy controls(HCs) were included. OCT was performed to measure peripapillary retinal nerve fiber layer(RNFL), ganglion cell layer(GCL), inner plexiform layer(IPL), central macular, and minimum foveal thicknesses(CMT and MFT), choroidal thickness(ChT). 4-hydroxy-2-nonenal(HNE), total thiol(TT), native thiol(NT), total oxidant status(TOS), total antioxidant status(TAS), disulfide(DIS) and oxidative stress index(OSI) were measured from serum samples. Results: TOS was higher patients with BD and FDRs than HCs (p < .001 and p = .012, respectively). OSI, DIS, HNE levels were higher patients with BD and FDRs than HCs (p < .001). TAS, TT, NT levels were lower patients and FDRs than HCs (p < .001). MFT of patients was thinner than HCs (p = .001). CMT of patients was thinner than HCs (p = .006); the same trend was observed in FDRs but did not reach the statistical significance level (p = .07). The groups did not differ on RNFL and choroidal thickness or GCL and IPL volume. Limitations: Evaluation of only a few retinal layers. Conclusions: TOS, TAS, OSI, TT, NT, DIS, HNE can be useful endophenotype biomarkers in BD. Among the OCT findings, CMT was determined as the closest parameter to being an endophenotype biomarker. Our study corroborates that oxidative stress parameters are more effective than OCT findings in endophenotype studies. © 2021 Elsevier B.V.
Keywords: Bipolar disorder; Endophenotype; Optical coherence tomography; Oxidative stress; Unaffetcted first-degree relatives